Telaah Etos Kerja Kepala Sekolah di SD Negeri 11 Indralaya Kabupaten Ogan Ilir - Septian Puja Kusuma (UNISAN JURNAL, 2024)
This research aims to investigate and analyze the work ethic of school principals at SD Negeri 11 Indralaya, Ogan Ilir Regency. Work ethic is an important factor in improving school performance and creating an effective learning environment. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with five school principals, direct observation in the school environment, and analysis of documents related to school management. The research results show that the work ethic of the principal at SD Negeri 11 Indralaya has various dimensions, including dedication, commitment, integrity and effective leadership. Factors that influence this work ethic include educational background, work experience, support from school staff, and pressure from the work environment. This research also identifies the challenges faced by school principals in maintaining and improving their work ethic, such as limited resources, policy changes, and complex task demands. The implication of this research is the importance of developing professionalism and ongoing support for school principals to increase their work ethic and improve the quality of education at SD Negeri 11 Indralaya, as well as other schools in similar areas. Future research could further explore the factors that influence school principals’ work ethic as well as effective strategies for improving that work ethic in the context of basic education.